Religious Pluralism in Thirteen Theses. Issue 1 (January 2016) - Schmidt-Leukel, Perry
Abstract : Thesis 1: In terms of our awareness of religions the world has become significantly smaller and each country significantly larger. Thesis 2: Both the factual presence and the awareness of religious diversity will continue to grow for an unforeseeable length of time. Thesis 3: The religious challenge of religious diversity emerges from the necessity to engage with the perception of different messages of salvation and corresponding truth claims. Thesis 4: For logical reasons there are only four basic options on how to interpret religious truth claims, and only three of them constitute religious options. Thesis 5 : Prima facie religious diversity seems to support an atheist/naturalist interpretation of religion. Thesis 6: Exclusivism is the weakest of all possible options. Thesis 7: Compared to exclusivism, inclusivism is only half-hearted progress. Thesis 8: Pluralism avoids the weak points of the two alternative options and represents a worthy alternative to atheism. Thesis 9: Religious pluralism is not relativism. Thesis 10: Religious pluralism is not in principle opposition to the actual religions. Thesis 11: Religious pluralism substantiates a new understanding of theology as 'interreligious theology'. Thesis 12: Religious pluralism offers a partial solution of the religious potential for conflicts. Thesis 13: On the social and political level the principle of tolerance takes precedence over religious pluralism.